Preparing superhydrophobic surfaces with very low contact angle hysteresis. (1st September 2013) - Huang, Y F; Huang, C; Zhong, Y L; Yi, S P
<x xml:space="preserve">Abstract</x> A low cost, large scale fabrication method of easily achieving superhydrophobic surfaces with very low contact angle hysteresis was reported in this paper. Microstructures were fabricated by the aggregation of the copolymer of styrene and methyl methacrylate using the phase separation method. Nanostructures were also achieved by the introduction of silica nanoparticles with hexamethyldisilazane modified surfaces into the copolymer. The presence of the nanoparticles significantly reduced the contact angle hysteresis of the superhydrophobic surface. The as prepared superhydrophobic surface had a large water contact angle of 162·3° and very low contact angle hysteresis of 1·7°. Hence, the method can enable the large scale fabrication of superhydrophobic surfaces with very low contact angle hysteresis on different substrates for practical applications.